Enhancing revisit intention through digital tourism experience and digital trust: the mediating role of tourist engagement in heritage tourism - Eko Yuliawan; Evilina Sjaiful; Sandi Noorzaman; Novie Nostalgia Adiwinata (Forum Kerjasama Pendidikan Tinggi, 2026)
This study analyzes the influence of Digital Tourism Experience and Digital Trust on Tourist Revisit Intention, with Tourist Engagement as a mediating variable, in heritage destinations at Borobudur Temple and Jakarta Old Town. Using a quantitative approach with SEM-PLS, data were collected from 134 respondents through an online questionnaire. The findings reveal that Digital Trust significantly affects Tourist Engagement and Tourist Revisit Intention, both directly and indirectly through the mediation of Tourist Engagement, whereas Digital Tourism Experience has a direct effect on Revisit Intention and does not significantly influence Tourist Engagement or the indirect pathways. Furthermore, Tourist Engagement plays a crucial role in driving revisit intention, confirming that emotional, cognitive, and social involvement are key mechanisms in fostering tourist loyalty. These results reinforce the applicability of the Theory of Planned Behavior (TPB) and the Technology Acceptance Model (TAM) in digital heritage tourism. Based on these findings, it is recommended that destination managers prioritize strengthening digital trust through reliable platforms, data security, and transparent communication, while also enhancing interactive and personalized digital features such as virtual tours, storytelling, and user-generated content to improve engagement; additionally, integrating digital and on-site experiences is essential to create a seamless tourist journey, and future studies are encouraged to expand the sample scope, include more diverse heritage destinations, and incorporate additional variables such as perceived value and satisfaction to enrich the research model.